The Importance Of Oil And Gas Sector For Libya: Current Scenario And Future Trends - Mohamed Ibrahim; Adel M.Abdulaziz; Mahazan Abdul Mutalib @ Talib (Australian Journal of Basic and Applied Sciences, 2024)
Non-Indexed Publication